Interpersonal Affective Touch in a Virtual World: Feeling the Social Presence of Others to Overcome Loneliness - Della Longa, Letizia; Valori, Irene; Farroni, Teresa (Frontiers in Psychology, 2022)
Humans are by nature social beings tuned to communicate and interact from the very beginning of their lives. The sense of touch represents the most direct and intimate channel of communication and a powerful means of connection between the self and the others. In our digital age, the development and diffusion of internet-based technologies and virtual environments offer new opportunities of communication overcoming physical distance. It however happens that social interactions are often mediated, and the tactile aspects of communication are overlooked, thus diminishing the feeling of social presence, which may contribute to an increased sense of social disconnection and loneliness. The current paper aims to review the extant literature about the socio-affective dimension of touch and current advancements in interactive virtual environments in order to provide a new perspective on multisensory virtual communication. Specifically, we suggest that interpersonal affective touch might critically impact virtual social exchanges, promoting a sense of co-presence and social connection between individuals, possibly overcoming feelings of sensory loneliness. This topic of investigation will be of crucial relevance from a theoretical perspective aiming to understand how we integrate multisensory signals in processing and making sense of interpersonal exchanges, this is important in both typical and atypical populations. Moreover, it will pave the way to promising applications by exploring the possibility to use technical innovations to communicate more interactively in the case of people who suffer from social isolation and disconnection from others.